Delinquent corporate management in the South African statutory context - Berthold, P J (Centre for Law and Society, 2026)
Full twenty years have passed since the publication of the main report of the Van Wyk-De Vries Commission of Enquiry into the companies Act1 and nearly twenty years have run since the promulgation of the present Companies Act. No 61 of 1973. In the interim a new corporate entity was introduced into South African law through the medium of the Close Corporations Act. No 69 of 1984. Both these Acts contain provisions which provide for the lifting of the corporate veil, which the Courts have shown a reluctance to do (save in cases concerning the fiscus), since the notion of a separate and distinct personality of a corporation distinct from the members who make it up was adopted in the Salamon saga. 2